Control and Performance of International Joint Ventures - Geringer, J. Michael; Hebert, Louis (Journal of International Business Studies, 1989)
Control is a critical concept for successful management and performance of international joint ventures (IJVs). This paper reviews and synthesizes prior studies addressing the conceptualization and operationalization of control within IJVs, as well as the IJV control-performance relationship. The paper also presents a new conceptualization of IJV control, as well as a conceptual frame work for studying control of IJVs.